Effectiveness Of Starfruit (Averrhoa bilimbi L.) Extract Against Head Lice (Pediculus humanus capitis) Mortality - Dini Athira; Rian Anggia Destiawan; Ahdiah Imroatul Muflihah (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2025)
Background: Head lice (Pediculus humanus capitis) are parasites that suck human blood. The disease caused by head lice is called Pediculosis which still occurs in densely populated areas such as Islamic boarding schools. The compounds contained in bilimbung wuluh fruit such as saponins and flavonoids are believed to help kill head lice. Purpose: This study aims to determine the effectiveness of star fruit extract (Averrhoa bilimbi L.) on the mortality of head lice (Pediculus humanus capitis). Methods: The method in this research is experimental with a Post Only Control Group research design. This study used 384 head lice samples with each group of 16 head lice samples sprayed with star fruit extract with concentrations of 10%, 20%, 30% and 40%. As well as using the gold standard anti-head lice drug Peditox and negative control in the form of sterile distilled water. Results: The results of this study indicate that star fruit extract (Averrhoa bilimbi L.) is effective in killing head lice (Pediculus humanus capitis) at concentrations of 20%, 30%, 40% within 30 minutes. However, at a concentration of 10% it is not effective in killing head lice. The Kruskal Wallis test showed that there was an effect of starfruit extract on head lice mortality with a significant value of 0.001 p-value ≤0.05. In the Maan-Whitney U follow-up test, it was found that there were differences in the test groups with a significant value of ≤0.05. However, in the 10% extract test group and the negative control group, there was no significant difference in values ≥0.05. Conclusions: Star fruit extract (Averrhoa bilimbi L.) is the most effective for killing head lice (Pediculus humanus capitis) within 30 minutes, namely a concentration of 40%.